2021
DOI: 10.1002/clc.23596
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of mobile health in alleviating risk factors related to the occurrence and development of coronary heart disease: A systematic review and meta‐analysis

Abstract: The association between the efficacy of mobile health and the occurrence and development of coronary heart disease (CHD) is still unclear. Mobile health can alleviate the risk factors for CHD. PubMed, EMbase, Web of Science, The Cochrane Library, CNKI, WanFang, and VIP databases were searched from inception through May 28, 2020. Randomized controlled trials of the effect of mobile health in alleviating the risk factors of CHD's occurrence and development were included. Risks of bias were assessed by two indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
(104 reference statements)
4
8
2
2
Order By: Relevance
“…In this sense, it is worth highlighting that only a few RCTs have measured waist circumference despite the positive correlation between abdominal obesity and atherosclerosis. This finding is in accordance with the results of Akinosum et al [ 43 ] and Huang et al [ 44 ] who also did not observe improvements in BMI; however, a recent meta-analysis [ 46 ] did find a reduction in BMI and waist circumference although few RCTs were included in the analysis. Moreover, each trial used a different kind of digital intervention (telephone calls, remote monitoring with smartphones, SMS text messages, medication reminder apps, conference call sessions, emails, or web apps).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this sense, it is worth highlighting that only a few RCTs have measured waist circumference despite the positive correlation between abdominal obesity and atherosclerosis. This finding is in accordance with the results of Akinosum et al [ 43 ] and Huang et al [ 44 ] who also did not observe improvements in BMI; however, a recent meta-analysis [ 46 ] did find a reduction in BMI and waist circumference although few RCTs were included in the analysis. Moreover, each trial used a different kind of digital intervention (telephone calls, remote monitoring with smartphones, SMS text messages, medication reminder apps, conference call sessions, emails, or web apps).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding SBP and DBP, our results agree with those obtained in recent meta-analyses [ 43 - 45 ]. However, they do not coincide with other meta-analyses that obtained improvements in DBP only [ 46 ]. They also do not coincide with the meta-analysis published by Kavradim et al [ 47 ], who observed improvements in both SBP and DBP.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Their self-management behaviors are influenced by many factors. For example, a negative psychological state can reduce the self-efficacy of patients and gradually erode their belief in treatment [ 16 , 17 ], while a low cognitive level may mislead patients into believing that PCI is a radical cure for CHD and restores their original living habits, which is not conducive to maintaining their nursing compliance [ 18 ]. Since CHD is a chronic disease, patients still need to maintain a positive attitude towards prevention and treatment after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…В целом схожих результатов удалось добиться нескольким исследовательским группам, результаты этих 4 РКИ были объединены в метаанализе Xu Y, et al: в группах пациентов со стабильной ИБС, в т.ч. после чрескожного коронарного вмешательства, ТМ вмешательство приводит к снижению показателей ОХС и ХС-ЛНП по сравнению с исходными и таковыми в группах контроля [24]. Необходимо подчеркнуть, что результаты первых нескольких месяцев наблюдения в ТМ программах зачастую не соответствуют окончательным.…”
Section: технические вопросы 7%unclassified